The relationship between servicescape elements towards employees’ satisfaction in the workplace / Nurul Afiera Fazira Mohd Amfal - Mohd Amfal, Nurul Afiera Fazira (Faculty of Business and Management, 2018)
This study is conducted to measure the influence of servicescape elements toward employees’ satisfaction in the workplace, emphasizing the respondents’ from similar background industry. The servicescape elements are build under three main dimensions, mainly is ambient conditions, space and functionality and signs and symbols. Meanwhile, the dependent variable to be measured under this concept is employees’ job satisfaction. The researcher has adopted the descriptive research on the issue. Then, the researcher’s sampling design is non-probability sampling which is convenience sampling method with 120 questionnaires were distributed to employees within the given time period. Data were collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The findings analysis includes the descriptive analysis, reliability testing, correlation and multiple regression analysis. The outcome of multiple regression analysis showed that ambient conditions, space and functionality and signs and symbols have a positive significant impact on employees’ satisfaction. In conclusion, it shows that the organization which provides good servicescape elements to the employees will ultimately enhance their satisfaction and improve organizational performance.